Beginning iOS AR game development : developing augmented reality apps with Unity and C# - Fowler, Allan (Professor) (Apress, 2019)
Create a fully featured application that's both sophisticated and engaging. This book provides a detailed guide in developing augmented reality games that can take advantage of the advanced capabilities of new iOS devices and code while also offering compatibility with still supported legacy devices. No programming experience is necessary as this book begins on the ground floor with basic programming concepts in Unity and builds to incorporating input from the real world to create interactive realities. You'll learn to program with the Unity 2017 development platform using C#. Recent announcements of increased AR capabilities on the latest iPhones and iPads show a clear dedication on Apple's part to this emerging market of immersive games and apps. Unity 2017 is the latest version of this industry leading development platform and C# is a ubiquitous programming language perfect for any programmer to begin with. Using the latest development technologies, Beginning iOS AR Game Development will show you how to program games that interact directly with the real world environment around the user for creative fantastic augmented reality experiences. What You'll Learn: Download assets from the Unity store ; Create a scene in Unity 2017 ; Use physics and controls on mobile devices. Who This Book Is For: Beginner programmers and/or people new to developing games using Unity. It also serves as a great introduction to developing AR games and educators teaching the subject at high school or higher levels.